2020
DOI: 10.1111/dom.14186
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent efficacy of the glucose‐dependent insulinotropic polypeptide (GIP) receptor antagonist GIP(3‐30)NH2 on GIP actions in humans

Abstract: The glucose‐dependent insulinotropic polypeptide (GIP) fragment GIP(3‐30)NH2 is a selective, competitive GIP receptor antagonist, and doses of 800 to 1200 pmol/kg/min inhibit GIP‐induced potentiation of glucose‐stimulated insulin secretion by >80% in humans. We evaluated the effects of GIP(3‐30)NH2 across a wider dose range in eight healthy men undergoing six separate and randomized 10‐mmol/L hyperglycaemic clamps (A–F) with concomitant intravenous infusion of GIP (1.5 pmol/kg/min; A–E) or saline (F). Clamps A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…For GIP, the doses of the antagonist employed have been demonstrated to block 80% of exogenous GIP when the latter was given in doses resulting in physiological elevations of GIP concentrations in plasma. A subsequent dose-response investigation gave similar results ( 12 ). Regarding GLP-1, the use of an antagonist as a tool for analyzing its actions is much more complicated.…”
Section: Introductionsupporting
confidence: 55%
“…For GIP, the doses of the antagonist employed have been demonstrated to block 80% of exogenous GIP when the latter was given in doses resulting in physiological elevations of GIP concentrations in plasma. A subsequent dose-response investigation gave similar results ( 12 ). Regarding GLP-1, the use of an antagonist as a tool for analyzing its actions is much more complicated.…”
Section: Introductionsupporting
confidence: 55%
“…11 Given that the GIP peak incidentally coincided with the decrease in upright SV; we hypothesize that this peptide, by increasing the splanchnic blood pooling, could contribute to the SV reduction and consequently to the worsening upright tachycardia. Indeed, a previous study 34 reported a significant increase in HR during infusion of the GIPR agonist GIP (1-42) and this effect was inhibited by the GIPR antagonist (GIP(3-30)N 2 ).…”
Section: Original Articlementioning
confidence: 93%
“…However, in T2DM patients, further studies to explore this problem were unable to be carried out due to the lack of appropriate GIP receptor antagonists. Recent studies have shown that GIP can improve glycemic control in patients with T2DM [ 39 , 40 ] and have revived studies on the development of novel antagonists [ 41 , 42 ]. These studies have led to a re-evaluation of the role of GIP in the anti-hyperglycemia of DPP4i.…”
Section: Dpp4 and Dpp4 Inhibitions In Diabetesmentioning
confidence: 99%